2021
DOI: 10.3389/fpsyg.2021.618537
|View full text |Cite
|
Sign up to set email alerts
|

Information Matching: How Regulatory Focus Affects Information Preference and Information Choice

Abstract: Individuals often prefer information that matches their needs. In this study, we aimed to explore the relationship between regulatory focus and information preference. Specifically, we investigated the effects of promotion-focused information and prevention-focused information on explicit and implicit information preferences and choice behavior, and examined the mediating roles of information preference. In Experiment 1, we found that prevention-focused individuals were more likely to choose functional informa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Prior research has shown that the RTs may relate to difficulties in decision-making and cognitive load ( Cowen et al, 2002 ; Wang et al, 2016 ). Also, the RTs for the matched tasks would be shorter than those for the unmatched jobs ( Wang and Wang, 2021 ). In the current study, promotion-focused consumers may fit more with the low IL condition than the high IL condition.…”
Section: Discussionmentioning
confidence: 99%
“…Prior research has shown that the RTs may relate to difficulties in decision-making and cognitive load ( Cowen et al, 2002 ; Wang et al, 2016 ). Also, the RTs for the matched tasks would be shorter than those for the unmatched jobs ( Wang and Wang, 2021 ). In the current study, promotion-focused consumers may fit more with the low IL condition than the high IL condition.…”
Section: Discussionmentioning
confidence: 99%
“…In other words, the pattern of behavior changes according to the focus type of self-regulation, which is a specific psychological need in an individual. Promotion focus, a self-regulation type that seeks to pursue pleasure, tends to improve one's current status in order to achieve the desired outcome and is a motivator sensitive to positive outcomes [56,57]. The focus on promotion is deeply related to advancement, growth, accomplishment, and enhancement.…”
Section: Regulatory Focimentioning
confidence: 99%
“…Self-regulation is the motivation to consciously change one's thoughts or behavioral responses in pursuit of goals or ideals. Many previous studies e.g., [54,57,63] have demonstrated that these regulatory motivations affect a wide range of psychological processes, such as emotions, memory, and approaches to problem-solving. There are various cases where self-regulation is needed in daily life, such as resistance to temptation, suppression of impulses to give up difficult tasks, and patience while experiencing psychological pain [56].…”
Section: Regulatory Focimentioning
confidence: 99%